Future Targets and Multiple Equilibria - GUHA, Ashok S. (Institutional Knowledge at Singapore Management University, 2005)
Multiple Pareto-rankable equilibria may obtain in an overlapping generations model where consumers save to reach a fixed target. Existence and uniqueness conditions are discussed. The model displays excess consumption sensitivity to current income and perfect old-age insurance.